Evaluation of the immune status of peripheral blood monocytes from dairy cows during the periparturition period - Hanako BAI; Talukder Md Abdus SHABUR; Hiroki KUNII; Tsukino ITOH; Manabu KAWAHARA; Masashi TAKAHASHI (The Journal of Reproduction and Development, 2019)
Calving is a critical but stressful event required for milk production in dairy cows. In the present study, we investigated the immune status of peripheral blood mononuclear cells (PBMCs) isolated from periparturient cows to better understand and, thus, possibly prevent stress during the periparturient period. To evaluate the immune response of PBMCs, we assessed their proliferation with or without a mitogen (concanavalin A, ConA). Blood samples were collected 24 h before and after calving and 1 week after calving. The proliferation of non-treated cells remained unchanged throughout the examination period. The immune response of PBMCs isolated from the cows before calving was relatively low, even after ConA stimulation; however, the immune response of PBMCs collected at both time points after calving was significantly higher than those of non-stimulated controls. Next, we examined the expression patterns of T cell related and inflammatory cytokine genes in PBMCs. We found that the mRNA expression levels of both CD4 and CD8 showed decreasing trends after calving. The expression of the Th1 cell marker gene IFNG also decreased after calving. The mRNA expression level of the inflammatory cytokine gene TNFA increased after parturition. Overall, our results suggest that the PBMC immune response was weakened in cows before delivery and part of the expression of the immune cell-related genes in these cells is altered 24 h before and after calving.